Pelayanan Terapi Akupunktur untuk Penurunan Skala Nyeri pada Masyarakat dengan Riwayat Gula Darah Tinggi - Ahmad Daffa' Aushof Aushof; Yessy Widhi Astuti; Fatimah Wahyu; Danang Aji Prabowo (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
Background: Pain is a common complaint in the community, especially among individuals with comorbidities such as high blood sugar, commonly known as Diabetes mellitus. Based on several existing studies, acupuncture can reduce pain levels in individuals with a history of high blood sugar. Objective: This community service activity aims to reduce pain scales in people with a history of high blood sugar in order to improve their quality of life. Methods: The program was conducted at the Sawah Besar Youth Center (Gelanggang Remaja Sawah Besar), Central Jakarta, involving 8 community members. The methods used included acupuncture therapy sessions along with education on preventing blood sugar spikes. The reduction in pain scale was measured using the Numeric Rating Scale (NRS) via pre-test and post-test, and then analyzed descriptively. Results: The pre-test results showed that 50% of the participants experienced severe pain, 50% moderate pain, and 0% mild pain. After the intervention, the pain scale decreased, resulting in 50% mild pain, 50% moderate pain, and 0% severe pain. This activity was effective in reducing pain scales in people with a history of high blood sugar; therefore, it needs to be continued and expanded with the support of related parties. Keywords: pain, diabetes mellitus, high blood sugar, acupuncture, community service